Pre-service teachers' beliefs, dispositions, and abilities regarding social justice and mathematics - McHugh, Maighread Lee (My University, 2011)
The purpose of this study was to examine pre-service teachers' beliefs, dispositions, and abilities to integrate social justice into the mathematics classroom during a one-semester mathematics methods course at a small, liberal arts university in the Midwest. The study examined their initial beliefs, attitudes, and abilities before engaging in a semester-long study of mathematics taught through a critical, social justice lens. Through purposeful modeling of social justice in the mathematics classroom, the study then gauged participants beliefs, dispositions, and abilities to integrate social justice concepts into the elementary mathematics curriculum.
Keywords: Teaching Materials.; Social justice - Study and teaching - United States.; Mathematics - Study and teaching (Elementary) - United States.; Teaching.